A mold-free, coating-free, easy-to-peel in-mold label film and its preparation method and application
By designing a mold-free and coating-free easy-to-peel label film, the ethylene-norbornene copolymer is used to achieve stable welding and easy-to-peel on high-density polyethylene bottles, and the traditional mold-in-destruction label film is not firmly pasted and recovered. The difficult problem reduces production costs and avoids pollution.
Patent Information
- Application Number
- CN202411533232.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-10-31
AI Technical Summary
The traditional in-mold label film is not firmly pasted on high-density polyethylene bottles, which is prone to labeling and continuous stripping, and is difficult to recycle. The coating process increases costs and environmental pollution.
Design a mold-free and non-coated easy-to-peel label film, including printing layer, support layer, bonding layer, subsurface layer and bonding layer, using ethylene-norbornene copolymer as thermal bonding material, through differentiated design The indicators of ethylene-norbornene copolymers achieve balance between anti-tension and welding strength, avoid molding and coating processes, and print ink directly on the surface of the printing layer.
It realizes stable welding and easy peeling between in-mold labels and high-density polyethylene bottles, reduces continuous stripping, reduces production costs, and can be classified and separated during recycling to avoid pollution.
Smart Images

Figure CN119036979B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of functional polypropylene films, in particular to a mold-pressing-free, coating-free and easily peelable in-mold label film and a preparation method and application thereof. Background Art
[0002] High-density polyethylene (HDPE) has good corrosion resistance and can be used as a packaging material for canned motor oil, pesticides, chemical liquids, cleaning products, food seasonings, etc. Usually, when high-density polyethylene is used as a packaging material, it is often necessary to use it with a label to use the label to identify the information of the packaged items and prevent counterfeiting.
[0003] The surface tension of high-density polyethylene is only 29-30mN / m. Traditional self-adhesive labels are not easily adhered to high-density polyethylene materials, and are prone to warping or even detachment. Especially when self-adhesive labels are attached to high-density polyethylene bottles (high-density polyethylene containers), when filled with hot liquids, the high-density polyethylene bottles will expand and contract. This change in volume will greatly reduce the adhesion of the self-adhesive labels. Therefore, the labeling method of high-density polyethylene bottles has gradually changed from self-adhesive labeling to in-mold labeling.
[0004] In-mold label film is generally used for in-mold labeling of high-density polyethylene bottles. During in-mold labeling, the temperature of the high-density polyethylene blank is generally 160-180℃, and the pressure is only 0.4-0.5MPa. In order to improve the welding strength of in-mold labeling, traditional in-mold label film generally uses low-melting-point polyolefin material as the bonding layer to weld and bond with the high-density polyethylene bottle.
[0005] However, on the one hand, these low-melting-point polyolefin materials reduce the crystallinity by introducing a second comonomer to polymerize with ethylene to obtain a lower melting point, such as the common ethylene-butene copolymer, ethylene-hexene copolymer, ethylene-octene copolymer and propylene-ethylene copolymer, etc., all reduce the melting point by introducing a second comonomer. However, the introduction of these second comonomers partially destroys the crystallization of polyethylene, resulting in the low-melting-point polyolefin materials not only having the characteristics of plastics, but also the characteristics of rubber. Based on the characteristics of rubber, these low-melting-point polyolefin materials have a higher room-temperature adhesion, which easily leads to the phenomenon of continuous sheets between the in-mold label films after production, especially after the in-mold label films are printed, die-cut, stacked and other processes to form multiple stacked in-mold labels, resulting in the inability to take out the in-mold label films one by one, and often taking out 2-3 in-mold labels at a time, resulting in 2 or 3 in-mold labels being placed in the mold, which seriously affects the in-mold labeling. In order to reduce the phenomenon of continuous stretching between in-mold labels, the related technology usually adopts a molding process to mold the surface of the bonding layer during the production process of the in-mold label film to form uneven textures, making the surface of the bonding layer rough and uneven, greatly reducing the effective contact area between the in-mold labels, thereby reducing the bonding force at room temperature and reducing the phenomenon of continuous stretching. However, the above-mentioned in-mold label film needs to adopt a molding process during production, which makes the production process complicated and the production cost high.
[0006] On the other hand, the in-mold label film using low-melting-point polyolefin material as the bonding layer has the problem of being too firmly bonded after being made into an in-mold label and welded to a high-density polyethylene bottle. It is difficult to separate the in-mold label from the high-density polyethylene bottle by simple peeling methods (for example, manual peeling), making it difficult to recycle the high-density polyethylene bottle as a single material (especially the in-mold label with ink will affect the pure recycling of high-density polyethylene).
[0007] On the other hand, in-mold label films generally need to be printed on their surface using printing methods such as flexographic printing, offset printing and rotary printing. Traditional in-mold label films generally have a layer of polyurethane or acrylic resin coating coated on the surface of the in-mold label film to meet printing needs. However, adding a coating process to the surface of the in-mold label film will increase costs. At the same time, the coating process will inevitably result in heat loss and organic solvent (VOCs) emissions, which is not in line with the trend of energy conservation and emission reduction. Summary of the invention
[0008] Based on this, the purpose of the present invention is to provide a mold-free, coating-free, easy-to-peel in-mold label film and a preparation method and application thereof. Compared with traditional in-mold label films, the mold-free, coating-free, easy-to-peel in-mold label film of the present invention reduces the post-processing molding process and avoids the occurrence of continuous sheeting; ink can be directly printed on the printing layer surface of the mold-free, coating-free, easy-to-peel in-mold label film, reducing the coating process and having good ink adhesion; after being made into an in-mold label and in-mold labeling on a high-density polyethylene bottle, the peeling force between the in-mold label and the high-density polyethylene bottle is moderate, and the high-density polyethylene bottle and the in-mold label can be separated by a simple peeling method (for example: manual peeling) and classified and recycled as single materials.
[0009] To achieve the above object, the present invention adopts the following technical solutions:
[0010] The first object of the present invention is to provide a mold-free, coating-free, easy-to-peel in-mold label film, comprising a printing layer, a support layer, a bonding layer, a sub-surface layer and a laminating layer arranged in sequence; the printing layer comprises ≥99.5wt% of maleic anhydride grafted propylene-ethylene copolymer; the support layer comprises polypropylene, titanium dioxide and calcium carbonate; the bonding layer comprises 50-59wt% of propylene-ethylene copolymer, 40-49wt% of ethylene-norbornene copolymer and 0.5-1wt% of antistatic agent; the sub-surface layer is composed of ethylene-norbornene copolymer. The present invention relates to a composite material comprising an ethylene-norbornene copolymer; the ethylene content in the ethylene-norbornene copolymer in the sub-surface layer is 38-40 mol%, and the glass transition temperature of the ethylene-norbornene copolymer in the sub-surface layer is 60-70°C; the laminating layer comprises ≥98wt% ethylene-norbornene copolymer, the ethylene content in the ethylene-norbornene copolymer in the laminating layer is 30-35 mol%, and the glass transition temperature of the ethylene-norbornene copolymer in the laminating layer is 80-100°C.
[0011] The mold-pressing-free, coating-free, and easily peelable in-mold label film of the present invention can avoid the occurrence of continuous sheets by coordinating the structures of each layer and designing the components of each layer, without the need for a mold-pressing process on the surface of the laminating layer, and can directly print ink without a coating process on the surface of the printing layer, and the ink has good adhesion. After the in-mold label made by printing and die-cutting the mold-pressing-free, coating-free, and easily peelable in-mold label film is used for in-mold labeling of high-density polyethylene bottles, its welding strength not only meets the in-mold labeling requirements, but also can be cleanly peeled off from the surface of the high-density polyethylene bottle by a simple peeling method (for example, manual peeling) during recycling, so as to separate the in-mold label and the high-density polyethylene bottle, and they are respectively recycled as single materials, thereby avoiding the problem of the material of the mold-pressing-free, coating-free, and ink on the surface of the in-mold label film remaining on the surface of the high-density polyethylene bottle, which causes the recycling of the high-density polyethylene bottle to be polluted.
[0012] The present invention takes into account the balance between the anti-stretching performance and the welding strength. The present invention adopts a non-crystalline material such as ethylene-norbornene copolymer as a thermal bonding material, and differentiates the indicators of the ethylene-norbornene copolymer in the sub-surface layer and the bonding layer, thereby achieving both the anti-stretching performance and the welding strength. The low ethylene content and high glass transition temperature of the ethylene-norbornene copolymer in the bonding layer are conducive to improving the anti-stretching performance; while the high ethylene content and low glass transition temperature of the ethylene-norbornene copolymer in the sub-surface layer are conducive to improving the welding strength.
[0013] The ethylene segment in the ethylene-norbornene copolymer can be welded with high-density polyethylene, and the norbornene segment is used as a glass transition temperature regulating segment of the thermal bonding material for adjusting the bonding force at room temperature. The present invention is designed that the ethylene content in the ethylene-norbornene copolymer in the bonding layer is 30-35 mol%, and the glass transition temperature of the ethylene-norbornene copolymer in the bonding layer is 80-100°C. The low ethylene content and high glass transition temperature of the ethylene-norbornene copolymer in the bonding layer are used to reduce the bonding force of the bonding layer at room temperature, and the occurrence of continuous stretching can be avoided without the molding process, and the ethylene-norbornene copolymer in the bonding layer and the high-density polyethylene bottle are guaranteed to have a certain welding strength. If the ethylene content in the ethylene-norbornene copolymer in the bonding layer is too low and the glass transition temperature is too high, the welding strength will be greatly reduced; if the ethylene content in the ethylene-norbornene copolymer in the bonding layer is too high and the glass transition temperature is too low, the room temperature adhesion of the bonding layer will be increased, and the phenomenon of continuous stretching will easily occur, affecting the labeling effect.
[0014] The present invention further considers that the low ethylene content and high glass transition temperature of the ethylene-norbornene copolymer in the laminating layer are insufficient to meet the welding strength between the in-mold label and the high-density polyethylene bottle. The present invention further improves the welding strength between the in-mold label and the high-density polyethylene bottle during in-mold labeling by providing the sub-surface layer. Considering that the ethylene content of the ethylene-norbornene copolymer in the laminating layer is low, a high content of ethylene is conducive to improving the welding strength. The present invention designs the ethylene content of the ethylene-norbornene copolymer in the sub-surface layer to be 38-40 mol%, and the glass transition temperature of the ethylene-norbornene copolymer in the sub-surface layer to be 60-70°C. By utilizing the high ethylene content and low glass transition temperature of the ethylene-norbornene copolymer in the sub-surface layer, when the in-mold label made by printing and die-cutting the mold-free and coating-free easy-to-peel in-mold label film is used for in-mold labeling of high-density polyethylene bottles, the ethylene-norbornene copolymer in the sub-surface layer can penetrate into the laminating layer and be welded to the high-density polyethylene bottle under the influence of temperature, and the ethylene-norbornene copolymer in the sub-surface layer and the ethylene-norbornene copolymer in the bonding layer are mutually infiltrated and entangled, thereby synergistically improving the welding strength between the in-mold label and the high-density polyethylene bottle, and further utilizing the sub-surface layer to achieve the effect of improving the welding strength. If the ethylene content in the ethylene-norbornene copolymer in the sub-surface layer is too high and the glass transition temperature is too low, it is easy to cause the welding strength with the high-density polyethylene bottle to be too high during in-mold labeling, resulting in some materials remaining on the surface of the high-density polyethylene bottle during peeling and recycling, causing recycling pollution. If the ethylene content in the ethylene-norbornene copolymer in the sub-surface layer is too low, based on the low ethylene content (30-35 mol%) in the ethylene-norbornene copolymer in the laminating layer, the welding strength cannot be effectively enhanced, affecting the labeling effect.
[0015] In addition, the conventional in-mold label film uses a low-melting polyolefin material as a laminating layer, wherein the low-melting polyolefin material is generally a copolymer with ethylene as the main component, and its ethylene content is generally above 60 mol%, so that the in-mold label made of the conventional in-mold label film is too firmly bonded to the high-density polyethylene bottle and is difficult to peel off manually. However, the ethylene content of the ethylene-norbornene copolymer in the sub-surface layer of the present invention is only 38-40 mol%, and the ethylene content of the ethylene-norbornene copolymer in the laminating layer is only 35-40 mol%, which are far lower than the ethylene content of the low-melting polyolefin material of the conventional in-mold label film, so that after the in-mold label made of the mold-free and coating-free easy-to-peel in-mold label film is used for in-mold labeling of high-density polyethylene bottles, the welding strength between the in-mold label and the high-density polyethylene bottle is controlled at 5-10N / 15mm, the welding strength is moderate, that is, the peeling force is moderate, and the separation of the in-mold label and the high-density polyethylene bottle can be achieved by manual peeling.
[0016] The present invention takes into account the complexity of the printing method of the traditional in-mold label film, which is to first coat and then print the ink. The present invention designs the components of the printing layer, and can directly print the ink on the surface of the printing layer, which reduces the coating process (i.e., coating-free) compared with the traditional in-mold label film. The printing layer uses ≥99.5wt% maleic anhydride grafted propylene-ethylene copolymer as the surface material, and not only utilizes the maleic anhydride group of the maleic anhydride grafted propylene-ethylene copolymer to have high polarity and reactivity, the high polarity is that it can have polar affinity with the ink, and the reactivity is that it can react with the hydroxyl, carboxyl and amine groups of the resin in the ink to form a chemical bond, but also the maleic anhydride grafted propylene-ethylene copolymer can increase the surface tension of the printing layer and delay the attenuation of the surface tension of the printing layer under the action of corona. The printing performance of the printing layer is improved by the above functions of the maleic anhydride grafted propylene-ethylene copolymer, and the high adhesion coating process can be eliminated, thereby reducing costs.
[0017] The support layer plays a role of mechanical support and includes polypropylene, titanium dioxide and calcium carbonate. The titanium dioxide plays a role of coloring and covering to reduce light transmittance; the calcium carbonate is mainly used for density adjustment and improving covering effect.
[0018] The function of the bonding layer is to connect the support layer and the sub-surface layer to avoid interlayer separation between the support layer, the bonding layer and the sub-surface layer. The bonding layer includes 50-59wt% propylene-ethylene copolymer, 40-49wt% ethylene-norbornene copolymer and 0.5-1wt% antistatic agent, and the function of the propylene-ethylene copolymer is to connect the polypropylene in the support layer and the ethylene-norbornene copolymer in the sub-surface layer to avoid interlayer separation between the sub-surface layer, the bonding layer and the sub-surface layer during the production of the mold-free and coating-free easy-to-peel in-mold label film, and at the same time, avoid the mold-free and coating-free easy-to-peel in-mold label film after printing and die-cutting to make an in-mold label for in-mold labeling of a high-density polyethylene bottle. During peeling and recycling, the interlayer separation between the support layer, the bonding layer and the sub-surface layer causes part of the material to fall off and remain on the high-density polyethylene bottle, affecting the classification and recycling of the in-mold label and the high-density polyethylene bottle. The function of the ethylene-norbornene copolymer in the bonding layer is to enhance the bonding force between the polypropylene connecting the support layer and the ethylene-norbornene copolymer of the sub-surface layer. In addition, the present invention, by adding the antistatic agent to the bonding layer, can, in the first aspect, prevent the mold-free, coating-free, easy-to-peel in-mold label film from generating static electricity during the preparation process, and avoid the phenomenon of continuous stretching due to static adsorption; in the second aspect, the support layer contains titanium dioxide and calcium carbonate, which have an oil absorption effect, and can make the antistatic agent migrate to the laminating layer in a directional manner, but not to the printing layer, and avoid small molecules migrating to the surface of the printing layer to affect the adhesion of ink; in the third aspect, the antistatic agent is added to the bonding layer to avoid the distance from the antistatic agent to the laminating layer being too short, resulting in thick sheets carrying water during casting and generating scale on the roller surface in the longitudinal stretching process.
[0019] As a preferred solution, the melt index of the ethylene-norbornene copolymer in the bonding layer, the ethylene-norbornene copolymer in the sub-surface layer and the ethylene-norbornene copolymer in the laminating layer is 2-5 g / 10 min (melt index test conditions: 230°C, 2.16 kg) to ensure melt flow matching between the bonding layer, the sub-surface layer and the laminating layer.
[0020] As a preferred solution, the ethylene content in the maleic anhydride grafted propylene-ethylene copolymer is 3-4 mol%. The ethylene content in the maleic anhydride grafted propylene-ethylene copolymer is designed to be 3-4 mol%, so that the surface of the printing layer obtains an excellent printing effect.
[0021] As a preferred solution, the melt index of the maleic anhydride grafted propylene-ethylene copolymer is 2.5-8 g / 10 min (melt index test conditions: 230° C., 2.16 kg). By limiting the melt index of the maleic anhydride grafted propylene-ethylene copolymer to the above range, it is helpful to ensure the melt flow matching between the printing layer and the support layer.
[0022] As a preferred solution, the printing layer further includes 0.1-0.5wt% anti-adhesive agent. Preferably, the average particle size of the anti-adhesive agent in the printing layer is 4-5µm, and the anti-adhesive agent in the printing layer is silicon dioxide or polymethyl methacrylate. By adding an anti-adhesive agent to the printing layer, the anti-adhesive effect of the mold-free, coating-free and easy-to-peel in-mold label film is improved. Silicon dioxide or polymethyl methacrylate is used as an anti-adhesive agent, and the average particle size of the anti-adhesive agent is 4-5µm, so that it can protrude from the printing layer to achieve an anti-adhesive effect. This is a conventional technical means in the art and will not be repeated here.
[0023] As a preferred solution, in the support layer, the polypropylene is homopolypropylene, the isotacticity of the homopolypropylene is 94-99%, and the melt index of the homopolypropylene is 2.5-3.5 g / 10 min (melt index test conditions: 230° C., 2.16 kg).
[0024] As a preferred solution, in the support layer, the addition ratio of the titanium dioxide in the support layer is 5-30wt%. The titanium dioxide used in the support layer is expensive. If the addition ratio of the titanium dioxide in the support layer is too high, the production cost of the mold-free, coating-free and easy-to-peel in-mold label film remains high; if the addition ratio of the titanium dioxide in the support layer is too high, the coloring and covering effect cannot be achieved, and the light transmittance is significantly improved. Preferably, the average particle size of the titanium dioxide is 0.25-0.35µm, and its synthesis process is a chlorination process.
[0025] As a preferred solution, in the support layer, the calcium carbonate is added in an amount of 5-20wt% in the support layer. The calcium carbonate used in the support layer is mainly used for density adjustment, and secondly, it is used to improve the covering effect at low cost. If the calcium carbonate is added in an amount too high in the support layer, it is easy to cause the mold-free, coating-free, and easy-to-peel in-mold label film to be easily separated during peeling and recycling after being used for in-mold labeling of high-density polyethylene bottles; if the calcium carbonate is added in an amount too low in the support layer, the density of the mold-free, coating-free, and easy-to-peel in-mold label film is too high, and the density adjustment effect cannot be achieved. Preferably, the average particle size of the calcium carbonate is 0.9-2µm.
[0026] As a preferred solution, the ethylene content in the propylene-ethylene copolymer is 11-16 mol%. The use of the propylene-ethylene copolymer with an ethylene content of 11-16 mol% is conducive to connecting the polypropylene in the support layer and the ethylene-norbornene copolymer in the sub-surface layer, and improving the interlayer bonding force between the sub-surface layer, the bonding layer and the sub-surface layer. If the ethylene content in the propylene-ethylene copolymer is too high, it is not conducive to the bonding force between the bonding layer and the support layer; if the ethylene content in the propylene-ethylene copolymer is too low, it is not conducive to the compatibility between the propylene-ethylene copolymer and the ethylene-norbornene copolymer in the bonding layer, and incompatibility between the two may occur.
[0027] As a preferred solution, in the bonding layer, the melt index of the propylene-ethylene copolymer is 2.5-8g / 10min (melt index test conditions: 230°C, 2.16kg) to ensure melt flow matching between the support layer, the bonding layer and the sub-surface layer.
[0028] As a preferred solution, the ethylene content in the ethylene-norbornene copolymer in the bonding layer is 38-40 mol%, and the glass transition temperature of the ethylene-norbornene copolymer in the bonding layer is 60-70° C. The composition of the ethylene-norbornene copolymer in the bonding layer is the same as that of the ethylene-norbornene copolymer in the sub-surface layer, which is beneficial to improve the bonding force between the bonding layer and the sub-surface layer.
[0029] As a preferred solution, in the printing layer, the maleic anhydride grafting rate of maleic anhydride grafted propylene in the maleic anhydride grafted propylene-ethylene copolymer is 0.8-1.3wt%. By limiting the maleic anhydride grafting rate of maleic anhydride grafted propylene in the maleic anhydride grafted propylene-ethylene copolymer to 0.8-1.3wt%, it is beneficial to ensure the polar affinity and reactivity between the printing layer and the ink, improve the printing performance of the printing layer, and directly print the ink on the surface of the printing layer, eliminating the coating process and reducing costs.
[0030] As a preferred solution, the laminating layer further comprises 1-2wt% of an anti-adhesive agent. By adding the anti-adhesive agent to the laminating layer, the anti-adhesive effect of the mold-free, coating-free and easy-to-peel in-mold label film is improved, and the occurrence of continuous stretching is further prevented. Preferably, the average particle size of the anti-adhesive agent in the laminating layer is 4-5µm, and the anti-adhesive agent in the laminating layer is silicon dioxide or polymethyl methacrylate.
[0031] As a preferred solution, the thickness of the printing layer is 1-1.5µm; the thickness of the supporting layer is 60-90µm; the thickness of the bonding layer is 3-5µm; the thickness of the sub-surface layer is 5-10µm; and the thickness of the laminating layer is 1-1.5µm.
[0032] The present invention further designs the thickness of each layer. The thickness of the printing layer is 1-1.5μm. Based on the average particle size of the anti-blocking agent of 4-5µm, if the thickness of the printing layer is less than 1µm, the anti-blocking agent is easy to fall off from the printing layer, contaminating the guide roller, causing the mold-free, coating-free, easy-to-peel in-mold label film to be easily scratched during the preparation process; if the thickness of the printing layer is higher than 1.5µm, the anti-blocking agent does not protrude from the printing layer high enough, causing the mold-free, coating-free, easy-to-peel in-mold label film to easily adhere, reducing the anti-adhesion effect. The thickness of the support layer is 60-90µm, which can play a role in mechanical support for the entire mold-free, coating-free, easy-to-peel in-mold label film, ensuring the coloring effect and covering effect. The thickness of the bonding layer is 3-5µm; if the thickness of the bonding layer is lower than 3µm, interlayer delamination is easy to occur between the support layer, the bonding layer and the sub-surface layer; if the thickness of the bonding layer is higher than 5µm, the film cost increases. The thickness of the sub-surface layer is 5-10µm, and the thickness of the bonding layer is 1-1.5µm. The present invention reduces the occurrence of continuous stretching while taking into account the welding strength with the high-density polyethylene bottle through the design of the thinner bonding layer and the thicker sub-surface layer.
[0033] The second aspect of the present invention is to provide a method for preparing any of the above-mentioned mold-free, coating-free, and easy-to-peel in-mold label films, comprising the following steps: melting each layer of raw material through an extruder, converging them at a co-extrusion die head to form an integrally formed thick sheet, and cooling the cast sheet, a longitudinal stretching process, a transverse stretching process, and a traction corona winding process to form the mold-free, coating-free, and easy-to-peel in-mold label film. The preparation process of the mold-free, coating-free, and easy-to-peel in-mold label film does not contain a molding process, and there will be no continuous stretching phenomenon. Based on the fact that no additional molding process and coating process are required, the present invention adopts an integrated molding processing method, which can greatly reduce labor costs, equipment purchases, and material costs, so that the mold-free, coating-free, and easy-to-peel in-mold label film of the present invention is not only beneficial to energy saving and environmental protection, but also has strong market competitiveness.
[0034] The third aspect of the present invention is to provide a use of any of the above-mentioned mold-pressing-free and coating-free easily peelable in-mold label films in high-density polyethylene bottles.
[0035] Specifically, the present invention first provides an application of any of the above-mentioned mold-free, coating-free, and easy-to-peel in-mold label films in in-mold labeling of high-density polyethylene bottles: the mold-free, coating-free, and easy-to-peel in-mold label films are subjected to printing (flexographic printing, offset printing, rotary printing, and other printing methods), die-cutting, stacking, and other processes to obtain a plurality of stacked in-mold labels (for example, 500 sheets / stack) (that is, each in-mold label includes an ink layer, a printing layer, a support layer, a bonding layer, a sub-surface layer, and a laminating layer arranged in sequence); a single in-mold label is grabbed by a manipulator and placed in a mold to form a mold with an in-mold label; high-density polyethylene is melted at 160-180° C., extruded through an annular mold to form a cylindrical blank, which is then placed in the above-mentioned mold with the in-mold label film, and then a blowing rod is inserted after the blank is cut. After ventilation, the blank expands, and the laminating layer of the in-mold label is welded together by the residual heat of the blank. Finally, after cooling, the in-mold label and the plastic part are integrated to form a high-density polyethylene bottle with an in-mold label.
[0036] Among them, in the process of the robot grabbing a single in-mold label and putting it into the mold, the in-mold label can be taken out individually without the phenomenon of continuous labels, that is, the robot will not grab 2 or 3 in-mold labels, avoid putting 2 or 3 labels into the mold, and prevent affecting the in-mold labeling.
[0037] The present invention further provides an easy-to-peel application of a mold-free, coating-free, and easily peelable in-mold label film on a high-density polyethylene bottle: after the high-density polyethylene bottle with the in-mold label is used, the in-mold label can be easily torn off by manual peeling, and no in-mold label material remains on the surface of the high-density polyethylene bottle. In this way, the in-mold label with ink and the high-density polyethylene bottle can be recycled separately, which is beneficial to the recycling of a single material, and is particularly suitable for transparent high-density polyethylene plastic bottles.
[0038] For better understanding and implementation, the present invention is described in detail below with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 A schematic diagram of a five-layer structure of a mold-pressing-free, coating-free and easily peelable in-mold label film of the present invention;
[0040] Figure 2 The present invention is a flow chart of a method for preparing a mold-free, coating-free and easily peelable in-mold label film;
[0041] Figure 3 It is a process flow chart of the application of a mold-pressing-free, coating-free and easily peelable in-mold label film of the present invention in in-mold labeling of high-density polyethylene bottles;
[0042] Figure 4 It is a schematic diagram of in-mold labeling of the in-mold label of the present invention on a high-density polyethylene bottle;
[0043] Figure 5 The present invention is a process flow chart of the easy-peel application of a mold-pressing-free and coating-free easy-peel in-mold label film on a high-density polyethylene bottle. DETAILED DESCRIPTION
[0044] In order to facilitate the understanding of the present invention, the present invention will be described more fully below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein.
[0045] As an embodiment of the present invention, the mold-free, coating-free and easy-to-peel in-mold label film can be referred to Figure 1 It is a five-layer structure, including a printing layer 1, a supporting layer 2, a bonding layer 3, a sub-surface layer 4 and a bonding layer 5 which are arranged in sequence.
[0046] The main components of each layer are as follows:
[0047] Printing layer 1: maleic anhydride grafted propylene-ethylene copolymer and anti-blocking agent;
[0048] Support layer 2: polypropylene, titanium dioxide (titanium dioxide) and calcium carbonate;
[0049] Tie layer 3: propylene-ethylene copolymer, ethylene-norbornene copolymer and antistatic agent;
[0050] Subsurface layer 4: ethylene-norbornene copolymer;
[0051] Adhesive layer 5: ethylene-norbornene copolymer and anti-blocking agent.
[0052] The mold-pressing-free and coating-free easy-to-peel in-mold label film of the present invention can be prepared by a biaxial stretching film-forming process, a cast film-forming process and a blown film-forming process, and the biaxial stretching film-forming process is preferably selected.
[0053] Specifically, based on the fact that no additional molding process and coating process are required, the present invention adopts an integrated molding processing method, which is specifically achieved through a co-extrusion-biaxial stretching process (i.e., a biaxial stretching film-forming process), including the following steps: each layer of raw materials is melted through an extruder respectively, and then gathered at a co-extrusion die to form an integrated thick sheet, and the molding-free, coating-free, and easy-to-peel in-mold label film is formed through casting, longitudinal stretching, transverse stretching, traction corona winding, aging treatment, and slitting processes.
[0054] See also Figure 2 , A is the raw material, B is the melt, C is the thick sheet, D is the film mother roll, E is the finished film, G is the extrusion process of the extruder, H is the quenching process, I is the biaxial stretching process, J is the corona-winding process, and K is the aging slitting process.
[0055] The specific production process is as follows: the screened raw materials A of each layer are premixed according to the designed formula, stirred evenly, and fed into each extruder after weighing and calculating the input ratio, and plasticized into melt B in the extruder extrusion process G. The melt is transported through a pipeline and filtered by a filter, and distributed to the die head through a flow channel for co-extrusion. After that, the melt B is formed into a thick sheet C through a sudden cooling process H of a chilled roller, and the thick sheet C is formed into a film through a biaxial stretching process I, wherein the biaxial stretching process can be a step-by-step biaxial stretching process of first longitudinal stretching and then transverse stretching, or a synchronous biaxial stretching process of longitudinal and transverse synchronous stretching. After cooling, trimming on both sides, pulling and measuring thickness, and corona-winding process J, the film master roll D is obtained. After the film master roll D is subjected to the aging and slitting process K, a finished film E is formed, i.e., the mold-free, coating-free and easy-to-peel in-mold label film.
[0056] The temperature of the extruder, flow channel, pipeline, filter and die head used in the above method is controlled at 230-260°C, the quenching temperature is controlled at 25-40°C, in the step-by-step stretching process, the process temperature of longitudinal and transverse stretching is controlled at 60-180°C, the longitudinal stretching ratio is controlled at 4.0-6.0 times, and the transverse stretching ratio is controlled at 7.0-10.0 times; in the synchronous stretching process, the process temperature of longitudinal and transverse stretching is controlled at 150-180°C, the longitudinal stretching ratio is controlled at 4.0-10.0 times, and the transverse stretching ratio is controlled at 4.0-10.0 times. After the biaxial stretching process I, the film can be cooled at room temperature, trimmed on both sides and pulled to measure thickness, rolled into a film mother roll D, and cut by aging K to finally obtain the finished film E, that is, the mold-free, coating-free and easy-to-peel in-mold label film.
[0057] The process flow of applying the five-layer structured free-mold pressing and free-coating easy-to-peel in-mold label film to in-mold labeling of high-density polyethylene bottles is as follows:
[0058] See also Figure 3 According to the common knowledge in the art, the finished film E (i.e., the mold-free, coating-free, and easy-to-peel in-mold label film) first undergoes a printing process P, which includes but is not limited to common processes such as rotary printing, offset printing, and flexographic printing, to obtain a semi-finished product M, and then undergoes a die-cutting process Q to obtain a single in-mold label N. The in-mold labels N are stacked together and placed on a label rack, and then go through a negative pressure label feeding process R and an in-mold labeling process S to finally obtain a high-density polyethylene plastic bottle O with an in-mold label.
[0059] Schematic diagram of in-mold labeling of the above-mentioned in-mold label on a high-density polyethylene bottle:
[0060] See also Figure 4, take out the in-mold label N from the label library through the negative pressure suction operation and put it into the mold. During the taking out process, the in-mold label N will not be taken out continuously. The in-mold label is fixed by the negative pressure condition of the mold. Then, a high-density polyethylene cylindrical blank is put in, the blank is cut, and a blowing rod is inserted to make the blank expand and form. The residual heat of the blank is used to fuse the bonding layers of the in-mold label together, and finally a high-density polyethylene bottle O with an in-mold label is formed.
[0061] The process flow of the easy-to-peel in-mold label film of the present invention for high-density polyethylene bottles is as follows:
[0062] See also Figure 5 The high-density polyethylene plastic bottle O with the in-mold label is manually peeled off to separate the in-mold label from the high-density polyethylene plastic bottle. After separation, no in-mold label material remains on the surface of the high-density polyethylene plastic bottle, realizing the classified recycling of the two materials and facilitating secondary utilization.
[0063] In the following examples or comparative examples:
[0064] Note 1: Determination of the welding strength between the in-mold label film and the high-density polyethylene film:
[0065] This test simulates the weld strength of the in-mold label film after in-mold labeling of high-density polyethylene bottles. A 100µm high-density polyethylene film is obtained through a casting process, and then a heat sealer (made by Brugger, Germany, model: HSG-C) is used to heat seal the in-mold label film and the high-density polyethylene film under the conditions of 135°C, 0.18MPa, and 1 second. After standing for 3 minutes under the test environment, the sample is cut into strips with a width of 15mm and a length of 15cm. Finally, the weld interface is peeled off and the weld strength is measured using a universal tensile tester (made by MTS Industrial Systems (China) Co., Ltd., model: CMT6502).
[0066] Note 2: Method for determining interlayer bonding strength:
[0067] This test calibrates the difficulty of interlayer peeling of in-mold label film. The laminating layer of the in-mold label film is subjected to offline corona treatment to make the surface tension of the laminating layer reach 60mN / m, and then the laminating layer of the in-mold label film is laminated with a high-viscosity tape. The pressure roller is rolled back and forth on the film surface at a speed of about 12cm / s under a dead weight of 2.5kg for three times. It is required that there are no bubbles between the in-mold label film and the high-viscosity tape. Then, after being placed in the test environment for 3 minutes, the sample is cut into strips with a width of 15mm and a length of 15cm. Finally, the in-mold label film and the high-viscosity tape are peeled off and the peeling force is measured with a universal tensile tester. If the peeling force is ≥15N / 15mm and the in-mold label film still does not delaminate between layers, it is evaluated as "no delamination"; if the peeling force is <15N / 15mm and the in-mold label film delaminates between layers, it is evaluated as "delamination". This is used to evaluate the difficulty of delamination between layers of the in-mold label film.
[0068] Note 3: Surface tension test method:
[0069] Tested according to national standard: GB / T 14216-2008.
[0070] Note 4: Printing effect test method:
[0071] The printing ink on the printed layer of the in-mold label film was printed using an offset colorimeter (manufactured by Foshan Chenpeng Electromechanical Co., Ltd., model: CP225-A) and a flexographic colorimeter (manufactured by Dongguan Liede Technology Co., Ltd., model: KY160). The surface was then cured using a UV curing machine (manufactured by Foshan Chenpeng Electromechanical Co., Ltd., model: CP30-20-1-B). After standing for 10 minutes, a high-viscosity tape was used to laminate the printed ink surface of the in-mold label film. The film was then rolled with a roller at a weight of 2.5 kg. Roll back and forth on the film surface at a speed of about 12 cm / s for three times. It is required that there are no bubbles between the in-mold label film and the high-viscosity tape. Then, after leaving it in the test environment for 3 minutes, the in-mold label film and the high-viscosity tape are peeled off and the ink adhesion is observed. If the ink does not fall off, it is evaluated as "excellent adhesion"; if the ink shedding area is less than 5%, it is evaluated as "good adhesion"; if the ink shedding area is 5-20%, it is evaluated as "medium adhesion"; if the ink shedding area is greater than 20%, it is evaluated as "poor adhesion".
[0072] Note 5: Surface resistivity test method:
[0073] Tested in accordance with national standard: GB / T 31838.3-2019, the testing instrument is surface resistivity meter (produced by SIMCO, Japan, model: ST-4).
[0074] Note 6: Room temperature adhesion test method:
[0075] The in-mold label film was pressed with a 10kg weight, and then placed in a 60°C oven for 30 minutes to simulate summer container transportation conditions. Finally, the bonding strength was tested using a film adhesion tester (produced by Dynisc, USA, model: D9047).
[0076] Note 7: Testing method for continuous sheet phenomenon:
[0077] The printed in-mold label film was die-cut into in-mold labels of size 10cm×10cm, 500 in number, and then stacked into a stack of in-mold labels and tied with rubber bands. A 10kg weight was used to press the stacked in-mold labels, and they were placed in a 60℃ oven for 30min. The rubber bands were untied, and the in-mold labels were taken out by a robot to observe the connection.
[0078] Example 1
[0079] This embodiment provides a mold-free, coating-free, and easily peelable in-mold label film. For its specific structure, please refer to Figure 1 , including a printing layer 1, a supporting layer 2, a bonding layer 3, a sub-surface layer 4 and a laminating layer 5 which are arranged in sequence.
[0080] in:
[0081] The printing layer 1 comprises: 99.5wt% maleic anhydride grafted propylene-ethylene copolymer (ethylene content is 4mol%, maleic anhydride grafting rate is 1.1wt%, melt index is 3g / 10min, melt index test conditions are: melting temperature is 230℃, load weight is 2.16kg) and 0.5wt% silicon dioxide (average particle size is 5µm);
[0082] The composition of the support layer 2 is: 70wt% homopolymer polypropylene (isotacticity is 97%, density is 0.905g / cm 3 , melt index is 3g / 10min, melt index test conditions: melting temperature is 230℃, load weight is 2.16kg), 15wt% titanium dioxide (chloride process, rutile type, average particle size is 0.3µm) and 15wt% calcium carbonate (average particle size is 1.2µm);
[0083] The composition of the bonding layer 3 is: 50wt% propylene-ethylene copolymer (ethylene content is 15mol%, melt index is 8g / 10min, melt index test conditions: 230℃, 2.16kg), 49wt% ethylene-norbornene copolymer (ethylene content is 40mol%, glass transition temperature is 60℃, melt index is 3g / 10min, melt index test conditions: melting temperature is 230℃, load weight is 2.16kg) and 1wt% glyceryl monostearate;
[0084] The sub-surface layer 4 comprises: 100 wt% ethylene-norbornene copolymer (ethylene content is 40 mol%, glass transition temperature is 60°C, melt index is 3 g / 10 min, melt index test conditions are: melt temperature is 230°C, load weight is 2.16 kg);
[0085] The laminating layer 5 comprises: 99 wt% ethylene-norbornene copolymer (ethylene content is 30 mol%, glass transition temperature is 100°C, melt index is 3 g / 10 min, melt index test conditions: melt temperature is 230°C, load weight is 2.16 kg) and 1 wt% silica (average particle size is 5 µm).
[0086] This embodiment also provides a method for preparing a mold-free, coating-free, and easily peelable in-mold label film. Figure 2 The specific production process is as follows: the screened raw materials A of each layer are premixed according to the designed formula, stirred evenly, and fed into each extruder after weighing and calculating the input ratio, and plasticized into melt B in the extruder extrusion process G. The melt is transported through a pipeline, filtered by a filter, and distributed to the die head through a flow channel for co-extrusion. After that, the melt B is formed into a thick sheet C through a sudden cooling process H of a chilled roller, and the thick sheet C is formed into a film through a biaxial stretching process I, wherein the biaxial stretching process I is a step-by-step double-stretching process of longitudinal stretching first and transverse stretching second. After the film is shaped, cooled, trimmed on both sides, traction thickness measurement, traction thickness measurement, corona treatment, and mother roll winding J, a film mother roll D is obtained. After the film mother roll D undergoes an aging and slitting process K, a film product E is formed, i.e., the mold-free, coating-free, and easy-to-peel in-mold label film.
[0087] The production equipment is a flat film method step-by-step biaxially oriented polypropylene production line provided by BRUECKNER of Germany. The main extruder (for the support layer 2) has a screw diameter of 150 mm and a length-to-diameter ratio of 33:1. The four auxiliary extruders (for the printing layer 1, the bonding layer 3, the sub-surface layer 4 and the laminating layer 5, respectively) are single screw extruders with a screw diameter of 120 mm and a length-to-diameter ratio of 30:1. The extruder temperature is 250°C in all sections except the feeding section, 250°C in the filter, flow channel and die section, and 30°C in the quenching (cast film) temperature. The corresponding temperatures of the preheating zone, stretching zone and shaping zone in the longitudinal stretching process are 140°C, 135°C and 140°C, and the roller surfaces in the above areas have Teflon coating as an anti-stick coating, and the stretch ratio is 5.0. The corresponding temperatures of the preheating zone, stretching zone and shaping zone in the transverse stretching process are 176°C, 157°C in the stretching zone, and 168°C in the shaping zone. The stretch ratio is 8.5, the production speed is 300 m / min, and the corona intensity on the surface of the printed layer is 40 W·min / m 2 .
[0088] The total thickness of the embossing-free and coating-free easy-to-peel in-mold label film of this embodiment is 105 μm, the printing layer 1 is 1 μm thick, the supporting layer 2 is 88 μm thick, the bonding layer 3 is 5 μm thick, the sub-surface layer 4 is 10 μm thick, and the laminating layer 5 is 1 μm thick.
[0089] The fusion strength between the mold-free and coating-free easy-to-peel in-mold label film and the high-density polyethylene film of this embodiment is 8.5N / 15mm, the interlayer bonding strength measurement: no delamination, the surface tension of the printing layer 1 is 50mN / m, the printing effect measurement: excellent adhesion, surface resistance: 10 11.5 Ω, the adhesive force at room temperature is 0g, and the continuous stretching phenomenon is measured: none.
[0090] The process flow of applying the mold-free, coating-free and peelable in-mold label film in this embodiment to in-mold labeling of high-density polyethylene bottles: Figure 3 The finished film E first undergoes a printing process P, which includes but is not limited to common processes such as rotary printing, offset printing, and flexographic printing, to obtain a semi-finished product M, and then undergoes a die-cutting process Q to obtain a single in-mold label N. The in-mold labels N are stacked together and placed on a label rack, and then go through a negative pressure label feeding process R and an in-mold labeling process S to finally obtain a high-density polyethylene plastic bottle O with an in-mold label.
[0091] In-mold label N In-mold labeling diagram of high-density polyethylene bottles: please refer to Figure 4 , take out the in-mold label N from the label library through the negative pressure suction operation and put it into the mold. During the taking-out process, the in-mold label N will not be taken out continuously. The negative pressure condition of the mold is used to fix the in-mold label film, and then the high-density polyethylene cylindrical blank is put in, the blank is cut, and the blowing rod is inserted to make the blank expand and form. The residual heat of the blank is used to fuse the bonding layers of the in-mold label film together, and finally a high-density polyethylene bottle O with an in-mold label is formed.
[0092] The process flow of the easy-peeling application of a mold-free and coating-free in-mold label film on a high-density polyethylene bottle in this embodiment is as follows: Figure 5 , the high-density polyethylene plastic bottle O with the in-mold label was manually peeled off to separate the in-mold label from the high-density polyethylene plastic bottle. After separation, no in-mold label material remained on the surface of the high-density polyethylene plastic bottle, realizing the classified recycling of the two materials and facilitating secondary utilization. Based on the interlayer bonding strength test, there was no stratification, indicating that the interlayer bonding strength was ≥15N / 15mm, which was much higher than the heat sealing strength of the in-mold label film and the high-density polyethylene film of 8.5 N / 15mm. The in-mold label film could be torn off from the surface of the high-density polyethylene plastic bottle without stratification, and no label material remained on the surface of the high-density polyethylene plastic bottle.
[0093] In order to compare the effects of the formulations of each layer on the performance, the following examples and comparative examples are designed based on Example 1, with only the proportions of the materials changed, and a systematic comparison is made in the form of a table. The details are as follows:
[0094] Example 2
[0095] This embodiment provides a mold-free, coating-free, and easily peelable in-mold label film, which is basically the same as Example 1, except that: the ethylene content in the ethylene-norbornene copolymer in the laminating layer 5 of the mold-free, coating-free, and easily peelable in-mold label film of this embodiment is 35 mol%, and the glass transition temperature is 80°C.
[0096] That is, in the mold-free, coating-free and easy-to-peel in-mold label film of this embodiment, the composition of the laminating layer 5 is: 99wt% ethylene-norbornene copolymer (ethylene content is 35mol%, glass transition temperature is 80°C, melt index is 3g / 10min, melt index test conditions: melting temperature is 230°C, load weight is 2.16kg) and 1wt% silicon dioxide (average particle size is 5µm).
[0097] Except for the above differences, the preparation method of the mold-pressing-free and coating-free easy-to-peel in-mold label film, the thickness of each layer, the in-mold labeling application process flow, the easy-to-peel application process flow, etc. of this embodiment are the same as those of Example 1.
[0098] Specifically, please refer to Table 1 for the formulation composition of each layer of the embossing-free and coating-free easy-to-peel in-mold label film of this embodiment and the performance test results.
[0099] Example 3
[0100] This embodiment provides a mold-free, coating-free, and easily peelable in-mold label film, which is basically the same as Embodiment 1, except that the content of ethylene in the maleic anhydride grafted propylene-ethylene copolymer in the printing layer 1 of the mold-free, coating-free, and easily peelable in-mold label film of this embodiment is 3 mol%.
[0101] That is, in the mold-free, coating-free and easily peelable in-mold label film of this embodiment, the components of the printed layer 1 are: 99.5wt% maleic anhydride grafted propylene-ethylene copolymer (ethylene content is 3mol%, maleic anhydride grafting rate is 1.1wt%, melt index is 3g / 10min, melt index test conditions: melting temperature is 230°C, load weight is 2.16kg) and 0.5wt% silicon dioxide (average particle size is 5µm).
[0102] Except for the above differences, the preparation method of the mold-pressing-free and coating-free easy-to-peel in-mold label film, the thickness of each layer, the in-mold labeling application process flow, the easy-to-peel application process flow, etc. of this embodiment are the same as those of Example 1.
[0103] Specifically, please refer to Table 1 for the formulation composition of each layer of the embossing-free and coating-free easy-to-peel in-mold label film of this embodiment and the performance test results.
[0104] Example 4
[0105] The present embodiment provides a mold-free, coating-free, and easily peelable in-mold label film, which is basically the same as Example 1, except that the ethylene content in the ethylene-norbornene copolymer in the sub-surface layer 4 of the mold-free, coating-free, and easily peelable in-mold label film of the present embodiment is 38 mol%, and the glass transition temperature is 65°C.
[0106] That is, in the mold-free, coating-free and easy-to-peel in-mold label film of this embodiment, the sub-surface layer 4 comprises: 100 wt% ethylene-norbornene copolymer (ethylene content is 38 mol%, glass transition temperature is 65°C, melt index is 3 g / 10 min, and melt index test conditions are: melting temperature is 230°C, and load weight is 2.16 kg).
[0107] Except for the above differences, the preparation method of the mold-pressing-free and coating-free easy-to-peel in-mold label film, the thickness of each layer, the in-mold labeling application process flow, the easy-to-peel application process flow, etc. of this embodiment are the same as those of Example 1.
[0108] Specifically, please refer to Table 1 for the formulation composition of each layer of the embossing-free and coating-free easy-to-peel in-mold label film of this embodiment and the performance test results.
[0109] Table 1 Formulation composition and performance test results of each layer of the mold-free and coating-free easy-to-peel in-mold label film of Examples 1-4
[0110]
[0111] Comparative Example 1
[0112] This comparative example provides an in-mold label film, which is basically the same as the in-mold label film without mold pressing and coating and easy to peel off in-mold label film in Example 1, except that: the ethylene content in the ethylene-norbornene copolymer in the laminating layer 5 of the in-mold label film of this comparative example is 40 mol%, and the glass transition temperature is 60°C.
[0113] That is, in the in-mold label film of this comparative example, the components of the laminating layer 5 are: 99wt% ethylene-norbornene copolymer (ethylene content is 40mol%, glass transition temperature is 60°C, melt index is 3g / 10min, melt index test conditions: melting temperature is 230°C, load weight is 2.16kg) and 1wt% silica (average particle size is 5µm).
[0114] Except for the above differences, the preparation method of the in-mold label film of this comparative example, the thickness of each layer, the in-mold labeling application process flow, and the easy-peel application process flow are the same as those of Example 1.
[0115] Specifically, please refer to Table 2 for the formulation composition of each layer of the in-mold label film of this comparative example and the performance test results.
[0116] Comparative Example 2
[0117] This comparative example provides an in-mold label film, which is basically the same as the mold-free, coating-free and easy-to-peel in-mold label film of Example 1, except that: the ethylene content in the ethylene-norbornene copolymer in the laminating layer 5 of the in-mold label film of this comparative example is 20 mol%, and the glass transition temperature is 158°C.
[0118] That is, in the in-mold label film of this comparative example, the composition of the laminating layer 5 is: 99wt% ethylene-norbornene copolymer (ethylene content is 20mol%, glass transition temperature is 158°C, melt index is 3g / 10min, melt index test conditions: melting temperature is 230°C, load weight is 2.16kg) and 1wt% silica (average particle size is 5µm).
[0119] Except for the above differences, the preparation method of the in-mold label film of this comparative example, the thickness of each layer, the in-mold labeling application process flow, the easy-peel application process flow, etc. are the same as those of Example 1.
[0120] Specifically, please refer to Table 2 for the formulation composition of each layer of the in-mold label film of this comparative example and the performance test results.
[0121] Table 2 Formulation composition and performance test results of each layer of the in-mold label film of Comparative Examples 1-2
[0122]
[0123] Comparative Example 3
[0124] This comparative example provides an in-mold label film, which is basically the same as the mold-free, coating-free and easy-to-peel in-mold label film of Example 1, except that: the ethylene content in the ethylene-norbornene copolymer in the sub-surface layer 4 of the in-mold label film of this comparative example is 44 mol%, and the glass transition temperature is 40°C.
[0125] That is, in the in-mold label film of this comparative example, the component of the sub-surface layer 4 is: 100wt% ethylene-norbornene copolymer (ethylene content is 44mol%, glass transition temperature is 40°C, melt index is 3g / 10min, melt index test conditions: melting temperature is 230°C, load weight is 2.16kg).
[0126] Except for the above differences, the preparation method of the in-mold label film of this comparative example, the thickness of each layer, the in-mold labeling application process flow, the easy-peel application process flow, etc. are the same as those of Example 1.
[0127] Specifically, please refer to Table 3 for the formulation composition of each layer of the in-mold label film of this comparative example and the performance test results.
[0128] Comparative Example 4
[0129] This comparative example provides an in-mold label film, which is basically the same as the mold-free, coating-free and easy-to-peel in-mold label film of Example 1, except that: the ethylene content in the ethylene-norbornene copolymer in the sub-surface layer 4 of the in-mold label film of this comparative example is 20 mol%, and the glass transition temperature is 158°C.
[0130] That is, in the in-mold label film of this comparative example, the component of the sub-surface layer 4 is: 100wt% ethylene-norbornene copolymer (ethylene content is 20mol%, glass transition temperature is 158°C, melt index is 3g / 10min, melt index test conditions: melting temperature is 230°C, load weight is 2.16kg).
[0131] Except for the above differences, the preparation method of the in-mold label film of this comparative example, the thickness of each layer, the in-mold labeling application process flow, the easy-peel application process flow, etc. are the same as those of Example 1.
[0132] Specifically, please refer to Table 3 for the formulation composition of each layer of the in-mold label film of this comparative example and the performance test results.
[0133] Table 3 Formulation composition and performance test results of each layer of the in-mold label film of Comparative Examples 3-4
[0134]
[0135] Comparative Example 5
[0136] This comparative example provides an in-mold label film, which is basically the same as the embossing-free, coating-free and easily peelable in-mold label film of Example 1, except that the content of ethylene in the maleic anhydride grafted propylene-ethylene copolymer in the printing layer 1 in the in-mold label film of this comparative example is 1 mol %.
[0137] That is, in the in-mold label film of this comparative example, the components of the printing layer 1 are: 99.5wt% maleic anhydride grafted propylene-ethylene copolymer (ethylene content is 1 mol%, maleic anhydride grafting rate is 1.1wt%, melt index is 3g / 10min, melt index test conditions: melting temperature is 230°C, load weight is 2.16kg) and 0.5wt% silicon dioxide (average particle size is 5µm).
[0138] Except for the above differences, the preparation method of the in-mold label film of this comparative example, the thickness of each layer, the in-mold labeling application process flow, the easy-peel application process flow, etc. are the same as those of Example 1.
[0139] Specifically, please refer to Table 4 for the formulation composition of each layer of the in-mold label film of this comparative example and the performance test results.
[0140] Comparative Example 6
[0141] This comparative example provides an in-mold label film, which is basically the same as the in-mold label film without mold pressing or coating and easy to peel off in-mold label film in Example 1, except that: no antistatic agent is added to the bonding layer 3 in the in-mold label film of this comparative example.
[0142] That is, in the in-mold label film of this comparative example, the composition of the bonding layer 3 is: 50wt% propylene-ethylene copolymer (ethylene content is 15mol%, melt index is 8g / 10min, melt index test conditions: 230°C, 2.16kg) and 50wt% ethylene-norbornene copolymer (ethylene content is 40mol%, glass transition temperature is 60°C, melt index is 3g / 10min, melt index test conditions: melting temperature is 230°C, load weight is 2.16kg).
[0143] Except for the above differences, the preparation method of the in-mold label film of this comparative example, the thickness of each layer, the in-mold labeling application process flow, the easy-peel application process flow, etc. are the same as those of Example 1.
[0144] Specifically, please refer to Table 4 for the formulation composition of each layer of the in-mold label film of this comparative example and the performance test results.
[0145] Table 4 Formulation composition and performance test results of each layer of the in-mold label film of Comparative Examples 5-6
[0146]
[0147] Comparative Example 7
[0148] This comparative example provides an in-mold label film, and its specific structure can be found in Figure 1 , including a printing layer 1, a supporting layer 2, a bonding layer 3, a sub-surface layer 4 and a laminating layer 5 which are arranged in sequence.
[0149] in:
[0150] The composition of the surface layer 1 is: 99.5wt% homopolymer polypropylene (isotacticity is 97%, density is 0.905g / cm 3 , melt index is 3g / 10min, melt index test conditions: melt temperature is 230℃, load weight is 2.16kg) and 0.5wt% silica (average particle size is 5µm);
[0151] The components of the support layer 2 are: 70wt% homopolypropylene (isotacticity is 97%, density is 0.905g / cm3, melt index is 3g / 10min, melt index test conditions: melting temperature is 230℃, load weight is 2.16kg), 15wt% titanium dioxide (chloride process, rutile type, average particle size is 0.3µm) and 15wt% calcium carbonate (average particle size is 1.2µm);
[0152] The composition of the bonding layer 3 is: 50wt% propylene-ethylene copolymer (ethylene content is 15mol%, melt index is 8g / 10min, melt index test conditions: 230℃, 2.16kg), 49wt% ethylene-butene copolymer (ethylene content is 65mol%, melting point temperature is 68℃, melt index is 8g / 10min, melt index test conditions: melting temperature is 190℃, load weight is 2.16kg) and 1wt% glyceryl monostearate;
[0153] The composition of the sub-surface layer 4 is: 100wt% ethylene-butene copolymer (ethylene content is 65mol%, melting point temperature is 68°C, melt index is 8g / 10min, melt index test conditions: melting temperature is 190°C, load weight is 2.16kg);
[0154] The laminating layer 5 comprises: 99 wt% ethylene-butene copolymer (ethylene content is 65 mol%, melting point is 68°C, melt index is 8 g / 10 min, melt index test conditions are: melting temperature is 190°C, load weight is 2.16 kg) and 1 wt% silicon dioxide (average particle size is 5 µm).
[0155] The preparation method of the in-mold label film of this comparative example, the thickness of each layer, the in-mold labeling application process flow, the easy-peel application process flow, etc. are the same as those of Example 1.
[0156] Specifically, please refer to Table 5 for the formulation composition of each layer of the in-mold label film of this comparative example and the performance test results.
[0157] Table 5 Formulation composition and performance test results of each layer of the in-mold label film of Comparative Example 7
[0158]
[0159] Please refer to Tables 1 to 5. The mold-pressing-free, coating-free, and easily peelable in-mold label film of the present invention, through the coordination of the structures of each layer and the design of the components of each layer, can avoid the occurrence of continuous sheets without performing a molding process on the surface of the bonding layer, and can directly print ink without performing a coating process on the surface of the printing layer, and the ink has good adhesion. After the in-mold label made by printing and die-cutting the mold-pressing-free, coating-free, and easily peelable in-mold label film is used for in-mold labeling of high-density polyethylene bottles, its welding strength not only meets the in-mold labeling requirements, but also can be peeled off from the surface of the high-density polyethylene bottle by peeling during recycling, so as to separate the in-mold label and the high-density polyethylene bottle, and they are separately recycled as single materials, thereby avoiding the problem of the material of the mold-pressing-free, coating-free, and easy-to-peel in-mold label film itself and the ink on the surface remaining on the surface of the high-density polyethylene bottle, causing pollution in the recycling of the high-density polyethylene bottle.
[0160] The ethylene content in the ethylene-norbornene copolymer in the heat-bonding layer 5 of the in-mold label film of Comparative Example 1 is too high and the glass transition temperature is too low. The in-mold label made of the in-mold label film of Comparative Example 1 has a large room-temperature adhesive force and is prone to continuous stretching, which affects the labeling effect.
[0161] The ethylene content in the ethylene-norbornene copolymer in the heat-bonding layer 5 of the in-mold label film of Comparative Example 2 is too low, and the glass transition temperature is too high. The welding strength between the in-mold label film of Comparative Example 2 and the high-density polyethylene film is 0. This test result simulates the welding strength of the in-mold label film after in-mold labeling of high-density polyethylene bottles, that is, the welding strength between the in-mold label made of the in-mold label film of Comparative Example 2 and the high-density polyethylene bottle is greatly reduced, and cannot be welded and bonded.
[0162] The ethylene content in the ethylene-norbornene copolymer in the sub-surface layer 4 of the in-mold label film of Comparative Example 3 is too high, and the glass transition temperature is too low. The welding strength between the in-mold label film of Comparative Example 3 and the high-density polyethylene film is relatively high. The test results simulate the welding strength of the in-mold label film after in-mold labeling of high-density polyethylene bottles, that is, the welding strength between the in-mold label made of the in-mold label film of Comparative Example 3 and the high-density polyethylene bottle is too high, resulting in part of the in-mold label material remaining on the surface of the high-density polyethylene bottle during peeling and recycling, resulting in recycling pollution.
[0163] The ethylene content in the ethylene-norbornene copolymer in the sub-surface layer 4 of the in-mold label film of Comparative Example 4 is too low, and the glass transition temperature is too high. The welding strength between the in-mold label film of Comparative Example 4 and the high-density polyethylene film is relatively low. The test results simulate the welding strength of the in-mold label film after in-mold labeling of high-density polyethylene bottles, that is, the welding strength between the in-mold label made of the in-mold label film of Comparative Example 4 and the high-density polyethylene bottle is relatively low, which affects the labeling effect.
[0164] The ethylene content in the maleic anhydride grafted propylene-ethylene copolymer in the printing layer 1 of the in-mold label film of Comparative Example 5 is too low, the surface tension of the printing layer 1 is relatively low, and the printing effect is relatively poor.
[0165] In the bonding layer 3 of the in-mold label film of Comparative Example 6, no antistatic agent is added, and the in-mold label made of the in-mold label film of Comparative Example 6 has a phenomenon of continuous expansion due to electrostatic adsorption.
[0166] In the in-mold label film of comparative example 7, homopolypropylene is used as the main material of the printing layer 1, instead of the maleic anhydride grafted propylene-ethylene copolymer of the present invention. The surface tension of the printing layer 1 is low, the printing effect is poor, and it is not suitable for direct surface printing. In addition, in the in-mold label film of comparative example 7, ethylene-butene copolymer is used in the bonding layer 3, the sub-surface layer 4, and the laminating layer 5. The in-mold label made of the in-mold label film of comparative example 6 has a large room temperature adhesion and a continuous stretching phenomenon. After in-mold labeling, the fusion strength with the high-density polyethylene bottle is too high, and part of the material of the in-mold label remains on the high-density polyethylene bottle when peeled off.
[0167] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and the present invention is also intended to include these modifications and modifications.
Claims
1. A mold-free, coating-free and easy-to-peel in-mold label film, characterized in that: It includes a printing layer, a supporting layer, a bonding layer, a sub-surface layer and a laminating layer which are arranged in sequence; The printing layer comprises ≥99.5wt% of maleic anhydride grafted propylene-ethylene copolymer; the maleic anhydride grafting rate of the maleic anhydride grafted propylene-ethylene copolymer is 0.8-1.3wt%; the ethylene content of the maleic anhydride grafted propylene-ethylene copolymer is 3-4mol; The support layer includes polypropylene, titanium dioxide and calcium carbonate; The bonding layer comprises 50-59wt% of propylene-ethylene copolymer, 40-49wt% of ethylene-norbornene copolymer and 0.5-1wt% of antistatic agent; The sub-surface layer is composed of ethylene-norbornene copolymer; the ethylene content of the ethylene-norbornene copolymer in the sub-surface layer is 38-40 mol%, and the glass transition temperature of the ethylene-norbornene copolymer in the sub-surface layer is 60-70° C.; The laminating layer comprises ≥98wt% of ethylene-norbornene copolymer, the ethylene content of the ethylene-norbornene copolymer in the laminating layer is 30-35mol%, and the glass transition temperature of the ethylene-norbornene copolymer in the laminating layer is 80-100°C.
2. The mold-free, coating-free and easily peelable in-mold label film according to claim 1, characterized in that: In the printing layer, the maleic anhydride grafted propylene-ethylene copolymer has a melt index of 2.5-8 g / 10 min under the test conditions of a melt temperature of 230° C. and a load weight of 2.16 kg.
3. The mold-free, coating-free and easily peelable in-mold label film according to claim 1, characterized in that: In the support layer, the polypropylene is homopolypropylene, the isotacticity of the homopolypropylene is 94-99%, and the melting index of the homopolypropylene under the test conditions of a melting temperature of 230° C. and a load weight of 2.16 kg is 2.5-3.5 g / 10 min.
4. The mold-free, coating-free and easily peelable in-mold label film according to claim 1, characterized in that: In the support layer, the addition ratio of the titanium dioxide in the support layer is 5-30wt%, and the average particle size of the titanium dioxide is 0.25-0.35µm; the addition ratio of the calcium carbonate in the support layer is 5-20wt%, and the average particle size of the calcium carbonate is 0.9-2µm.
5. The mold-free, coating-free and easily peelable in-mold label film according to claim 1, characterized in that: In the bonding layer, the ethylene content in the propylene-ethylene copolymer is 11-16 mol%, and the melt index of the propylene-ethylene copolymer under the test conditions of a melting temperature of 230° C. and a load weight of 2.16 kg is 2.5-8 g / 10 min; the ethylene content in the ethylene-norbornene copolymer in the bonding layer is 38-40 mol%, and the glass transition temperature of the ethylene-norbornene copolymer in the bonding layer is 60-70° C.
6. The mold-free, coating-free and easily peelable in-mold label film according to claim 1, characterized in that: The melt index of the ethylene-norbornene copolymer in the bonding layer, the ethylene-norbornene copolymer in the sub-surface layer and the ethylene-norbornene copolymer in the laminating layer is 2-5 g / 10 min under the test conditions of a melting temperature of 230° C. and a load weight of 2.16 kg.
7. The mold-free, coating-free and easily peelable in-mold label film according to claim 1, characterized in that: The printing layer further comprises 0.1-0.5 wt % of an anti-adhesive agent; and the laminating layer further comprises 1-2 wt % of an anti-adhesive agent.
8. The mold-free, coating-free and easily peelable in-mold label film according to claim 1, characterized in that: The thickness of the printing layer is 1-1.5µm; the thickness of the supporting layer is 60-90µm; the thickness of the bonding layer is 3-5µm; the thickness of the sub-surface layer is 5-10µm; and the thickness of the laminating layer is 1-1.5µm.
9. A method for preparing a mold-free, coating-free, easily peelable in-mold label film according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: melting each layer of raw materials through an extruder respectively, and converging them at a co-extrusion die to form an integrally formed thick sheet; and cooling the cast sheet, longitudinally stretching, transversely stretching, and pulling corona winding to form the mold-free, coating-free, and easily peelable in-mold label film.
10. Use of the mold-pressing-free, coating-free and easily peelable in-mold label film according to any one of claims 1 to 8 in high-density polyethylene bottles.